Implementasi Cash Management System Menggunakan Real-Time Payment untuk Optimalisasi Layanan Sistem Koperasi Simpan Pinjam Sekolah - Bayumi, Firman Ahmad; Parabi, M. Iqbal; Wulansari, Ossy Dwi Endah; Sholehurrohman, Ridho (Jurnal Manajemen Informatika JAMIKA, 2025)
School savings and loan cooperatives that are still run conventionally cause various problems such as delays in recording, the risk of human error, and the potential for data loss. This research aims to develop a savings and loan cooperative system that implements a Cash Management System to improve the cooperatives financial recording and management processes and use of the Real-Time Payment feature to accelerate the cooperatives savings and loan transaction processes. This research uses the Extreme Programming method. This method includes planning, design, coding, and testing. System testing includes functional testing using Selenium IDE showing results in accordance with the required scenarios, non-functional testing using Apache JMeter which indicated the need for further evaluation of performance under concurrent user requests, and User Acceptance Testing obtained a percentage of 68.2% for administrators and 84.4% for members, with an overall satisfaction index of “Very Good."